Forests and society: sustainability and life cycles of forests in human landscapes - Edited by K.A. Vogt....[et al] (Oxfordshire, 2006)
This book provides a broad-ranging textbook on the relationships between forests and society. It discusses the ways in which society can interact with forest landscapes without adversely affecting their sustainability. Topics covered include attitudes to, and uses of forests, the creation of today's forest landscapes, the impact of humans on forests, and forest sustainability and human health. The book also examines emerging issues in forestry such as possible solutions to balancing societies' needs with forest sustainability, managing forests in the urban-wildland interface, and the impact of illegal logging. It is packed with real-world case studies from the USA, Australia, Bolivia, Botswana, Canada, China, Iceland, India, Indonesia, Kenya, Mexico, Nepal, Peru, Philippines, Puerto Rico, and Thailand.
Keywords: Forest and forestry